The Effect of the Problem-Based Learning Model on 21st Century Student Skills: A Meta-Analysis - Sisrayanti; Maksum, Hasan; Waskito; Sabrina, Elsa (AI Society & STMIK Indonesia, 2024)
This study aims to investigate the impact of Problem Based Learning (PBL) on the development of 4C skills (Critical Thinking, Creativity, Collaboration, Communication) among students. Through meta-analysis, data from 20 national and international journal articles published between 2018 and 2023 were analyzed. Findings indicate that the consistent use of PBL yields a highly significant effect, with an average effect size of 1.72. These results affirm the effectiveness of PBL in enhancing students' 4C skills, underscoring the importance of this instructional approach in the context of 21st-century education, which emphasizes critical thinking, creativity, collaboration, and communication skills. The practical implications of this study highlight the necessity of integrating PBL models in instructional design to facilitate the development of 21st-century skills among students. Further research could delve into specific aspects of PBL usage and its impacts on student learning outcomes and academic achievement.